Construcción de un índice para la identificación de una burbuja inmobiliaria en Bogotá (2017)
The main motivation for the current paper is the high speculation over the housing prices in Bogotá. As happened on 2008 in the U.S, a crisis locally would be alarming for investors being one of the main catalyzers of a financial crisis. The document explains, through the construction of a housing price index, the historical behavior of prices as well as a future forecast for the contextualization of the hypothesis that surrounds the real estate sector in the last years, the possible presence of a bubble in market prices.--Tomado del Formato de Documento de Grado.